Carotenoid-based coloration predicts both longevity and lifetime fecundity in male birds, but testosterone disrupts signal reliability - Cantarero Alejandro; Pérez-Rodríguez Lorenzo; Romero-Haro Ana Ángela; Chastel Olivier; Alonso-Alvarez Carlos (Public Library of Science, 2022)
Sexual selection promotes the evolution of conspicuous animal ornaments. To evolve as
signals, these traits must reliably express the “quality” of the bearer, an indicator of individual
fitness. Direct estimates of individual fitness may include the contribution of longevity and
fecundity. However, evidence of a correlation between the level of signal expression and
these two fitness components are scarce, at least among vertebrates. Relative fitness is dif-
ficult to assess in the wild as age at death and extra-pair paternity rates are often unknown.
Here, in captive male red-legged partridges, we show that carotenoid-based ornament
expression, i.e., redness of the bill and eye rings, at the beginning of reproductive life pre-
dicts both longevity (1–7 years) and lifetime breeding output (offspring number and hatching
success). The recently proposed link between the individual capacity to produce red (keto)
carotenoid pigments and the efficiency of cell respiration could, ultimately, explain the
correlation with lifespan and, indirectly, fecundity. Nonetheless, in males of avian species,
carotenoid-based coloration in bare parts is also partially controlled by testosterone. We
also manipulated androgen levels throughout life by treating males with testosterone or anti-
androgen compounds. Treatments caused correlations between signal levels and both fit-
ness components to disappear, thus making the signals unreliable. This suggests that
the evolution of carotenoid-based sexual signals requires a tightly-controlled steroid
metabolism.